Suzaku observation of the unidentified very high energy gamma-ray source HESS J1702-420 - Fujinaga, Takahisa; Bamba, Aya; Dotani, Tadayasu; Ozaki, Masanobu; Pühlhofer, Gerd; Wagner, Stefan; Reimer, Olaf; Funk, Stefan; Hinton, Jim (Publications of the Astronomical Society of Japan, 2011)
A deep X-ray observation of the unidentified very high energy (VHE) gamma-ray source HESS J1702 − 420, for the first time, was carried out by Suzaku. No bright sources were detected in the XIS field of view (FOV), except for two faint point-like sources. The two sources, however, are considered not to be related to HESS J1702 − 420, because their fluxes in the 2–10 keV band ( ∼ 10 −14 erg s −1 cm −2 ) are ∼ 3 orders of magnitude smaller than the VHE gamma-ray flux in the 1–10 TeV band ( FTeV= 3.1 × 10 −11 erg s −1 cm −2 ). We compared the energy spectrum of diffuse emission, extracted from the entire XIS FOV with those from nearby observations. If we consider the systematic error of background subtraction, no significant diffuse emission was detected with an upper limit of FX< 2.7 × 10 −12 erg s −1 cm −2 in the 2–10 keV band for an assumed power-law spectrum of Γ= 2.1 and a source size same as that in the VHE band. The upper limit of the X-ray flux is twelve-times as small as the VHE gamma-ray flux. The large flux ratio ( FTeV/FX ) indicates that HESS J1702 − 420 is another example of a “dark” particle accelerator. If we use a simple one-zone leptonic model, in which VHE gamma-rays are produced through inverse Compton scattering of the cosmic microwave background and interstellar far-infrared emission, and the X-rays via the synchrotron mechanism, an upper limit of the magnetic field (1.7 μ G) is obtained from the flux ratio. Because the magnetic field is weaker than the typical value in the galactic plane (3–10 μ G), the simple one-zone model may not work for HESS J1702 − 420 and a significant fraction of the VHE gamma-rays may originate from protons.
Gesehen am 01.06.2023